2016
DOI: 10.1021/acs.est.6b00235
|View full text |Cite
|
Sign up to set email alerts
|

Organoarsenical Biotransformations by Shewanella putrefaciens

Abstract: Microbes play a critical role in the global arsenic biogeocycle. Most studies have focused on redox cycling of inorganic arsenic in bacteria and archaea. The parallel cycles of organoarsenical biotransformations are less well characterized. Here we describe organoarsenical biotransformations in the environmental microbe Shewanella putrefaciens. Under aerobic growth conditions, S. putrefaciens reduced the herbicide MSMA (methylarsenate or MAs(V)) to methylarsenite (MAs(III)). Even though it does not contain an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…Four different species of bacteria, Pseudomonas putida KT2440 (Yoshinaga et al , ), Burkholderia sp. MR1 (Yoshinaga et al , ), Shewanella putrefaciens 200 (Chen and Rosen, ) and Sinorhizobium meliloti RM1021 are capable of reducing MAs(V), demonstrating that multiple soil bacteria have the ability to reductively generate MAs(III). Neither E. coli ArsC (Oden et al , ) nor yeast Acr2p (Mukhopadhyay et al , ) reduce MAs(V) (unpublished results), and the pathway/genes/enzymes involved in MAs(V) reduction are as yet unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four different species of bacteria, Pseudomonas putida KT2440 (Yoshinaga et al , ), Burkholderia sp. MR1 (Yoshinaga et al , ), Shewanella putrefaciens 200 (Chen and Rosen, ) and Sinorhizobium meliloti RM1021 are capable of reducing MAs(V), demonstrating that multiple soil bacteria have the ability to reductively generate MAs(III). Neither E. coli ArsC (Oden et al , ) nor yeast Acr2p (Mukhopadhyay et al , ) reduce MAs(V) (unpublished results), and the pathway/genes/enzymes involved in MAs(V) reduction are as yet unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Several bacterial strains have been identified that are capable of reducing MAs(V), including the environmental isolate Burkholderia sp. MR1 (Yoshinaga et al , ), as well as S. putrefaciens 200 (Chen and Rosen, ), P. putida KT2440 (Yoshinaga et al , ), and S. meliloti RM1021. To date, no specific genes/enzymes involved in MAs(V) reduction have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In S. putrefaciens 200, the arsenic ars cluster consists of 19 genes, which are regulated by three different arsR genes (Chen and Rosen, ). One, termed SparsR (accession number: ADV53698), is novel in its gene product has a two‐cysteine arsenic binding motif and lacks a third ligand for binding of inorganic As(III) compared to characterized ArsRs such as R773 ArsR, CgArsR and AfArsR.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that formation of thioarsenicals is non-enzymatic but does not eliminate the possibility of enzymatic pathways of synthesis. Environmental microbes such as Shewanella putrefaciens also thiolate methylated arsenicals, producing MMMTAs(V) and DMMTAs(V) (Rubin et al, 2014;Chen and Rosen, 2016). However, its mechanism is similarly, poorly understood.…”
Section: Thiolorganoarsenicalsmentioning
confidence: 99%